HAKEKAT ORGANISASI PERANGKAT DAERAH (Suatu Tinjauan Teoritis dan Yuridis) - Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Existence Governance of visible Area see section 18 sentence of UUD RI of Year 1945 expressing that governance of authoritative area to arrange and manage xself Business of Governance [of] according to Autonomous Ground and the Aid Duty. Along the happening of growth [in] area of governance specially the area governance, governmental of Number 23 Year 2014 about Governance of Area in the place of of Number 32 Year 2004. In assisting to run business of konkuren and business of the governance, hence Regional Leader of Kabupaten/Kota assisted by area peripheral. Peripheral of Area [of] pursuant to UU of Number 23 Year 2014 consisted of; Area secretariat, Secretariat DPRD, Inspectorate, On duty Area and Area Body, and also for kabupaten/Kota of peripheral of area added with subdistrict. In compiling organization of peripheral of area have to pay attention to kewenangan of area in system of governance of area as follow-up from business of governance divided clearly in UU of Number 23 Year 2014. nomenclature And basaran on duty have to relate [at] business of governance delivered to area and overflowed [by] kewenangannya to Governor and Bupati/Walikota. In realisasinya of name on duty which there (be) still unlike name of business which carrying out of. And there [is] on duty carrying out business which is non becoming business of konkuren with sub of kewenangan of area which berasngkutan. Therefore, pengelompokkan of governmental institution with the title on duty, body and office own separate concept in study of governance science. [Is] so that needed [by] existence of sighting return to mention on duty, body, and office [of] exist in area which is generally have meng-implementasikan of by law [of] about Organization of Peripheral of Area start january 2017